2022
DOI: 10.1038/s41598-022-11736-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of cachexia index in patients with advanced hepatocellular carcinoma treated with systemic chemotherapy

Abstract: Cancer cachexia affects quality of life, response to chemotherapy, and survival in many advanced cancer patients. The aim of this study was to evaluate the prognostic value of pretreatment cachexia index (CXI) in patients with advanced hepatocellular carcinoma (HCC) treated with systematic chemotherapy. Patients with advanced HCC treated with lenvatinib therapy between October 2018 and October 2020 were retrospectively studied. The CXI was calculated as (L3 skeletal muscle index) × (serum albumin)/(neutrophil-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…All these features are included in the CXI and might therefore be desirable to measure cancer cachexia. Recent studies reported that CXI had significant associations with survival in patients with lung cancer, liver cancer, biliary tract cancer, and aggressive lymphomas [ 15 , 20 , 21 , 22 , 23 ]. However, the prognostic value of CXI in patients with GC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…All these features are included in the CXI and might therefore be desirable to measure cancer cachexia. Recent studies reported that CXI had significant associations with survival in patients with lung cancer, liver cancer, biliary tract cancer, and aggressive lymphomas [ 15 , 20 , 21 , 22 , 23 ]. However, the prognostic value of CXI in patients with GC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Cachexia index (CXI), a new measure of cachexia, is consisted of three objective indicators including SMI, serum albumin, and neutrophil-lymphocyte ratio (NLR) (11). Recent studies have indicated that CXI is significantly associated with treatment response and prognosis in patients with malignancies such as lung cancer, liver cancer, and aggressive lymphomas (11)(12)(13)(14)(15). In this study, we aim to evaluate the prognostic value of CXI in patients with colorectal cancer, which might be helpful to distinguish the potentially cachexic patients.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, an optimal cutoff of 72.7 for men and 57.1 for women was established for CXI using ROC curve analysis, respectively, but at a cutoff of 35, CXI also predicted poor survival in patients with lung cancer in a univariate and multivariate analysis study [11]. A CXI cutoff of 49.8 (median) [12] also predicted poor survival in patients with diffuse large B-cell lymphoma, while in patients with hepatocellular carcinoma [19], a CXI cutoff of 53 predicted poor survival. Cumulatively, these results supported CXI in gauging survival in patients with different cancers.…”
Section: Discussionmentioning
confidence: 99%